Employment shocks and anti-EU sentiment - Marie Lechler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2018)
Euroscepticism and the rise of populist parties have often been linked to economic insecurity. This paper identifies regional employment changes as causal factors for forming attitudes towards the European Union and voting for eurosceptic parties in European Parliament elections. To do so, I combine industry-specific employment data for roughly 260 European NUTS II regions with individual-level Eurobarometer survey data for the past 20 years and regional voting results. I apply panel data and instrumental variable methods; for the latter I construct a Bartik-style instrument, which predicts employment changes on the basis of regional industry specialization and Europe-wide sector specific employment growth rates. The effect of employment changes on attitudes towards the EU is particularly strong for unemployed and low-skilled workers in regions with a high share of migrants from other European member states, which supports the narrative that "losers of globalization" tend to be more skeptical towards economic and political integration.
urn:nbn:de:bvb:19-epub-49414-2
Keywords: E24; F66; F68; J21; O52; P16; 330; European Integration; Regional Employment; EU Attitudes; European Parliament Elections; EU Migration